Academic Stress and Its Association with Gingivitis Among Preclinical Dental Students at Universitas Muhammadiyah Semarang: A Cross-Sectional Study - Berlian Shinta Faradiansyah; Yanuarita Tursinawati; Ayuda Nur Sukmawati (Indonesian Dental Association, 2026)
Introduction: Stress is an adaptive process and a natural response by individuals to environmental demands. However, excessive stress can negatively impact periodontal health, leading to gingivitis. Gingivitis can develop due to hormonal changes mediated by the Hypothalamic-Pituitary axis (HPA) and the sympathetic autonomic nervous system (ANS), as well as due to behavioural changes. Dental students facing frequent exposure to stressors will be at a heightened vulnerability. Objective: This study aimed to determine the association between academic stress levels, measured using the Perception of Academic Stress Scale (PASS), and gingival status, assessed using the Löe and Silness Gingival Index, among preclinical dental students at Universitas Muhammadiyah Semarang. Methods: This correlational study employed a cross-sectional design. The study population consisted of preclinical dental students from the 2020–2023 cohorts at Universitas Muhammadiyah Semarang. A total of 69 participants were selected using stratified random sampling. Academic stress was assessed using the Perception of Academic Stress Scale (PASS), while gingival status was evaluated through intraoral examination using the Gingival Index. The association between academic stress and gingival status was analyzed using Spearman’s correlation test. Results: A statistically significant positive correlation was found between academic stress levels and gingivitis (Spearman's rho = 0.309, p = 0.010), indicating a weak-to-moderate association. Conclusion: The findings indicate a statistically significant positive association of weak-to-moderate strength between academic stress and gingivitis among preclinical dental students at Universitas Muhammadiyah Semarang.